Formulating Research Problem in Academic Writing: Indonesian Expert Authors' Cognitive Experience - Fadhly, Fahrus Zaman (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
This research aims to reconstruct the cognitive process in formulating research problems in writing scientific journal articles. Through a grounded theory approach, this study reveals six important findings related to the formulation of research problems in scientific journal articles, i.e.: a gap between expectations and reality; intensive search by finding possibilities, norm testing results and case studies; mapping global structure of issues; and data replication. This research concludes that the formulation of research problems in writing scientific journal articles is identical to the research gap (RG). As an empty space or a vast space of possibilities, RG can be entered and examined more deeply and seriously by researchers in various disciplines so that they can explore and discover new knowledge. This research has an important and significant impact on the development of science and technology. It offers a new approach to how cognitive experiences were constructed. The results of the construction of this cognitive process have tangible benefits for many people regarding how research problems and research questions are formulated.